Simple vs. complex transitive constructions in the acquisition of English structures - Sánchez Calderón, Silvia (Círculo de Lingüística Aplicada a la Comunicación, 2021)
This study examines the acquisition of English simple monotransitive and complex dative alternation (DA) structures (double object constructions (DOC) and to/for-datives) in the longitudinal spontaneous production of monolingual children. In order to address these issues, we analyzed data from twelve English monolingual children and from adults’ child-directed speech, as available in CHILDES (MacWhinney, 2000). The findings revealed that simple monotransitive constructions started being produced earlier and showed a higher incidence when compared to complex DA constructions, which suggests that the degree of syntactic complexity has had an effect on the acquisition of transitives. However, the two complex DA constructions emerged at an approximately similar age, which could be explained by the Case assigning related properties. Furthermore, the chronological progression and the difference regarding the incidence of the three constructions (monotransitives > DOCs > to/for-datives) could be attributed to the amount of exposure to these structures in the adult input.